Reliable PCR amplification from Neurospora crassa genomic DNA obtained from conidia - Steven T. Henderson; Graham A. Eariss; David E. A. Catcheside (Fungal Genetics Reports, 2005)
Boil-mediated lysis of Neurospora conidia (Boil-prep) is an extremely rapid, convenient and useful technique to obtain sufficient genomic DNA template for PCR amplification. We routinely use this technique for screening molecular markers, sequencing, and preliminary confirmation of transformants.